DINAMIKA UMKM BATIK JAMBI SEBERANG PADA MASA PANDEMI COVID- 19 TAHUN 2020 - Indah Sari, Zalvia (Krinok: Jurnal Pendidikan Sejarah dan Sejarah, 2024)
The COVID-19 pandemic has had quite a bad impact on all sectors, especially the economic sector. Where many entrepreneurs are experiencing the impact of Covid-19, such as losses and going out of business, this is due to economic instability. One of the supports for the Indonesian economy is the existence of MSMEs which create jobs and provide opportunities for Batik MSMEs, especially in Jambi Seberang, to develop among the community. This research method uses qualitative research methods with the Batik Jambi Seberang MSME research location. The aim of this research is to find out how the journey or dynamics of Jambi Seberang Batik MSMEs were during the COVID-19 period in 2020. The results of the research show that Batik MSMEs in Jambi Seberang continued to run their businesses even though they were hindered by COVID-19, they continued to sell even though the results obtained were small. decrease. However, they can solve this problem by attracting customers' attention again by carrying out marketing promotions via social media to attract customers.